Perturbative super-Yang-Mills from the topological AdS 5 × S 5 sigma model - Berkovits, Nathan [UNESP] (Int School Advanced Studies, 2008)
A topological sigma model based on the pure spinor formalism was recently proposed for the small radius limit of the AdS 5 × S 5 superstring. Physical states in this model can be constructed by connecting holes on the worldsheet with Wilson lines of the worldsheet gauge field. The contribution of these states to the topological amplitude is claimed to reproduce the usual Feynman diagram expansion of gauge-invariant super-Yang-Mills correlation functions. © 2008 SISSA.
Keywords: AdS-CFT correspondence; Topological strings